Differences in biomass partitioning, leaf nitrogen content, and water use efficiency (δ13C) result in similar performance of seedlings of two Mediterranean oaks with contrasting leaf habit (Ecoscience, 2005)
Co-occurrence of winter-deciduous and evergreen oaks is common in some Mediterranean-type climate areas. However, whether these species show an overlap in their regeneration niche is still poorly understood. We explored experimentally the changes in survival, growth, biomass partitioning, leaf nitrogen content, and water use efficiency (δ13C) in seedlings of a deciduous oak (Quercus cerrioides) and an evergreen oak (Quercus ilex) in response to co-variation in light and water availability. Quercus cerrioides exhibited higher root length, root area, leaf nitrogen content, and less negative δ13C, but lower leafiness than Q. ilex. The interaction between species and light in specific leaf area and root–shoot ratio indicated different mechanisms to overcome water stress in the two oaks, with Q. ilex relying on leaf hardening and Q. cerrioides relying on a high root–shoot ratio. However, the two species showed similar survival and growth in most of the light–water gradient. Ecological inference of these results indicates that seedlings of these species have a similar ability to cope with variations in light and water in spite of their contrasting leaf habit. This similar performance suggests a competition for similar micro-sites during establishment, rather than a partitioning of the regeneration niche.